'Absolutely free'? The role of relational work in sustaining artistic innovation. Issue 6 (June 2016) - Montanari, Fabrizio; Scapolan, Annachiara; Gianecchini, Martina
Drawing on the relational perspective of artistic innovation, which suggests that different types of ties (weak vs. strong) lead to different outcomes in terms of the development and implementation of new artistic ideas, this study uses an in-depth case study of Italian choreographer Mauro Bigonzetti to explore the role of the relational work artists deploy to develop and implement their artwork. We investigate how artists engage in specific relational actions (broadening, bonding, embedding and dis-embedding) with producing organizations, and how these actions lead to innovation over time. The findings suggest that artistic innovation moves through four stages – proximal innovation, fuzzy innovation, established innovation and maintained innovation – sustained by an artist's oscillation between a network characterized by strong ties with few organizations and a network characterized by weak ties with many organizations, depending on the artist's quests for inclusion and differentiation. In this process, a long-lasting relationship between the artist and a specific organization may 'pivot' artistic innovation.